Comparison of the modified subvastus and medial parapatellar approaches in total knee arthroplasty - Jung, Young Bok (Springer-Verlag, 2008)
In this paper, we evaluated the difference between the modified subvastus approach and the medial parapatellar approach in total knee arthroplasty(TKA). We assessed the time of active straight-leg raise (SLR) post-operatively and the range of flexion of the operated knee at the tenth post-operative day, 6 weeks and 6 months, 12 months and 3 years. We investigated the degree of the patellar tilt and subluxation 24 months post-operatively. The patients who underwent the modified subvastus approach performed active SLR earlier (mean 0.5 days) than the medial parapatellar approach patients (mean 2.2 days). Knee flexion was better at the tenth post-operative day in the modified subvastus approach group compared to the medial parapatellar approach group. There was no statistical difference between the two groups with regard to the patellar tilt and subluxation. We conclude that the modified subvastus approach is recommendable in primary TKA.